Novel approaches to modular multiport DC power systems - Fares, Ahmed Mohamed (2019)
New trends in radar remote sensing satellites are aiming to implement small, low cost satellites instead of large ones. Radar imaging payloads currently targeting small satellite platforms require peak powers of ≥1kW, whilst the peak power capability of these satellites is at present limited to 100-200W. This calls for new power system designs that meet the new power requirements imposed by these trends, but with a restricted weight/volume budget to fit this platform. In this research, a novel modular multiport converter (MMPC) is proposed. It enables higher voltage power buses without the need to build PV/battery strings with a large number of series connected cells, which can result in a poor utilization of available PV energy and battery capacity. It also removes the need for additional battery cell/module equalizer circuitry by being able to directly implement energy management strategies that can adapt to different of battery modules. The converter modes of operation, control strategy and design considerations are presented. A 75V/1kW integrated power system prototype is built and tested to validate the proposed concept. An optimized energy storage system considering a radar imaging payload power profile is also investigated based on different devices (Li-ion batteries, electric double layer capacitors (EDLC) and Li-ion capacitors). A hybrid system consisting of Li-ion batteries/EDLC was found to be the optimal solution considering overall weight and thermal stress on the energy storage devices. However, conventional converters for interfacing the EDLC limit the utilization of its nominal energy capacity to 75% resulting in larger sizes. Therefore, a novel multiport converter that enables maximum utilization of EDLC energy capacity is also proposed. It allowed a 20% size reduction in the EDLC stack for the same energy capacity. Furthermore, a size reduction for the converter inductors could be achieved by a novel interleaved modulation technique proposed. The converter modes of operation, control strategy and design considerations are derived and experimentally validated on the same converter prototype that was reconfigured accordingly.